Stabilization and electronic topological transition of hydrogen-rich metal Li5MoH11 under high pressures from first-principles predictions - Prutthipong Tsuppayakorn-aek (Nature Portfolio, 2021)
Abstract Regarded as doped binary hydrides, ternary hydrides have recently become the subject of investigation since they are deemed to be metallic under pressure and possibly potentially high-temperature superconductors. Herein, the candidate structure of Li5MoH11 is predicted by exploiting the evolutionary searching. Its high-pressure phase adopts a hexagonal structure with P63/mcm space group. We used first-principles calculations including the zero-point energy to investigate the structures up to 200 GPa and found that the P63cm structure transforms into the P63/mcm structure at 48 GPa. Phonon calculations confirm that the P63/mcm structure is dynamically stable. Its stability is mainly attributed to the isostructural second-order phase transition. Our calculations reveal the electronic topological transition displaying an isostructural second-order phase transition at 160 GPa as well as the topology of its Fermi surfaces. We used the projected crystal orbital Hamilton population (pCOHP) to examine the nature of the chemical bonding and demonstrated that the results obtained from the pCOHP calculation are associated with the electronic band structure and electronic localized function.